Adenosine Receptor Stimulation by Polydeoxyribonucleotide Improves Tissue Repair and Symptomology in Experimental Colitis - Pallio, Giovanni; Bitto, Alessandra; Pizzino, Gabriele; Galfo, Federica; Irrera, Natasha; Squadrito, Francesco; Squadrito, Giovanni; Pallio, Socrate; Anastasi, Giuseppe P.; Cutroneo, Giuseppina; Macrì, Antonio; Altavilla, Domenica (Frontiers in Pharmacology, 2016)
Activation of the adenosine receptor pathway has been demonstrated to be effective in improving tissue remodelling and blunting the inflammatory response. Active colitis is characterized by an intense inflammatory reaction resulting in extensive tissue damage. Symptomatic improvement requires both control of the inflammatory process and repair and remodelling of damaged tissues. We investigated the ability of an A2A receptor agonist, polydeoxyribonucleotide (PDRN), to restore tissue structural integrity in two experimental colitis models using male Sprague-Dawley rats. In the first model, colitis was induced with a single intra-colonic instillation of dinitro-benzene-sulfonic acid (DNBS), 25mg diluted in 0.8ml 50% ethanol. After 6 hrs, animals were randomized to receive either PDRN (8mg/kg/i.p.), or PDRN + the A2A antagonist (DMPX; 10mg/kg/i.p.), or vehicle (0.8 ml saline solution) daily. In the second model, dextran sodium sulphate (DSS) was dissolved in drinking water at a concentration of 8%. Control animals received standard drinking water. After 24 hrs animals were randomized to receive PDRN or PDRN+DMPX as described above. Rats were sacrificed 7 days after receiving DNBS or 5 days after DSS. In both experimental models of colitis, PDRN ameliorated the clinical symptoms and weight loss associated with disease as well as promoted the histological repair of damaged tissues. Moreover, PDRN reduced expression of inflammatory cytokines, myeloperoxydase activity, and malondialdheyde. All these effects were abolished by the concomitant administration of the A2a antagonist DMPX. Our study suggests that PDRN may represent a promising treatment for improving tissue repair during inflammatory bowel diseases.